The importance of Digital-based Payment Management Knowledge for MSME Drivers: a Study of Financial Literacy - Jenita Jenita; Amrih Yuwono; Tutik Heriana; Susantriana Dewi; Mila Diana Sari (Budapest International Research and Critics University, 2022)
Along with the demands of an increasingly modern world, productivity and efficiency services are also demanded in all circles, including those who drive the medium-sized business economy. One of the most phenomenal currently implementing all human business activities is digital payment technology in serving their business. The author believes that the effectiveness resulting from the burning of various digitals in the management of small MSMEs can lead the business to be profitable and sustainable. So to whiten and complete the discussion of this call to prayer, we have conducted a series of data testing and interpretation of the data analysis with high validity and reliability. The literature sources we found were electronic digestion of many publications, especially books, scientific articles, and relevant website information to answer the hypothesis of this study. So, based on the data analysis and discussion, we can summarize the importance of knowledge and experience in managing digital technology-based payments for those who drive the small business economy, which is now constantly competing. Confidence in the effectiveness of using payments in this way has been proven and has been recommended by experts, as we mentioned in the results and discussion sections. It is hoped that this finding will also enrich scientific knowledge, especially digital-based payments for small business drivers in the country.